SAT0257 "aiming for the bullseye": retinal toxicity screening for hydroxychloroquine therapy – are we hitting the target?. (15th June 2017) - Gubbins, S; Steen, J; Gorman, A; Khan, S; Mohammad, A; O'Rourke, K
Abstract : Background: Hydroxychloroquine (HCQ) is commonly used to treat a variety of rheumatological and inflammatory conditions such as RA, SLE and Sjogrens. Retinal toxicity is a well known complication of HCQ therapy. Initially, the incidence of retinal toxicity was believed to be quite minimal1. However, subsequent large epidemiological studies have highlighted its much greater prevalence-up to 7.5% in certain populations2, 3. Furthermore, the visual toxicity is typically permanent with possible progression up to years after drug cessation and with no current treatment4. Detection at an early stage has been shown to be crucial in preserving central vision and foveal architecture5. As a result ophthalmological screening is an essential consideration for any patient on HCQ therapy. In view of the updated scientific data available on toxicity prevalence and the benefits of screening, the American Academy of Ophthalmology (AAO) have updated their screening recommendations for 20166. This includes baseline fundus examination to rule out pre-existing maculopathy and annual screening after 5 years of treatment. Objectives: To investigate compliance with the AAO Recommendation on Screening for Chloroquine and Hydroxychloroquine Retinopathy (2016)6 in a regional rheumatology centre. Methods: A retrospective analysis was undertaken of the electronic patient records of 161 patients with a diagnosis of connective tissue disease at a single regional centre assessing level of antimalarial usage, adherence to screening guidelines and level of documented toxicity. Results: Of our cohort, 91 (56%) were on regular HCQ. Of these, 12 had received routine ophthalmology screening and 4 developed documented ocular toxicity. 15 suffered non-ophthalmic toxicity requiring therapy cessation. 46 had been on therapy greater than 5 years and of these 9 (21.5%) had been screened. Conclusions: Our analysis revealed significant deficiencies in routine screening and demonstrated a high level of toxicity in patients who were routinely screened. This indicates that there may be a significant number of patients with toxicity that is not being picked up and reinforces the importance of screening. We would recommend a more streamlined referral pathway for rheumatology patients on HCQ and hypothesise that this would lead to greater and earlier pick-up of ocular toxicity in this population, ultimately reducing morbidity in this population. References: Elman A, Gullberg R Nilsson E, et al. Chloroquine retinopathy in patients with rheumatoid arthritis. Scand J Rheumatol. 1976;5(3):161–66. Melles RB, Marmor MF. The risk of toxic retinopathy in patients on long-term hydroxychloroquine therapy. JAMA Ophthalmol 2014;132:1453–60. Levy GD, Munz SJ, Paschal J, et al. Incidence of hydroxychloroquine retinopathy in a large multicentered outpatient practice. Arthritis Rheum. 1997 Aug;40(8):1482–6. Marmor MF, Hu J. Effect of disease stage on progression of hydroxychloroquine retinopathy. JAMA Ophthalmol 2014;132:1105–12. Marmor MF, Hu J. Effect of disease stage on progression of hydroxychloroquine retinopathy. JAMA Ophthalmic 2014;132:1105–12. Michael F, Marmor MD et al, Recommendations on Screening for Chloroquine and Hydroxychloroquine Retinopathy (2016 Revision) Ophthalmology Volume 123, Number 6, June 2016. Disclosure of Interest: None declared